Determinants of Sustainable Tourism Destinations in Indonesia - SILABAN, Pasaman; ADHITYA, Wisnu Rayhan; KHAERUMAN, Khaeruman; DACHI, Surya Wisada; AFRIANI, Joli; AISYAH, Siti; SITORUS, Sunday Ade (Journal of Environmental Management and Tourism, 2023)
The purpose of this study is to investigate the tourism concept variable, tourism services and facilities and infrastructure affect the success variable of developing sustainable tourism destinations through moderating variables of tourist interest to visit. In this study, the independent variable is related to the development of sustainable tourism destinations, the variable is the concept of tourism, tourism services and facilities and infrastructure, while the dependent variable is the success in developing the concept of sustainable tourism, and the moderating variable is the interest of tourists to visit. The research method used in this study is a quantitative descriptive research method using path analysis. In this study the independent variables are related to factors related tothe development of sustainable tourism destinations, such as tourism concept variables, tourism services and facilities and infrastructure, the dependent variable is the success in developing the sustainable tourism concept, with moderating variable (connecting variable) tourist interest to visit, data analysis using AMOS 20, and data taken is data on the number of tourist visits to Indonesia during 2016-2020 years. Partially variable tourism concept, tourism services and infrastructure advice significant effect on the variable successful development of tourist destinations and has a significant effect on the variable of tourist interest in visiting 5 priority tourist destinations in Indonesia, while simultaneously the variable tourism concept, tourism services and infrastructure advice indirectly has a significant effect on the variable successful development of tourist destinationsthrough the interest of tourists to visit 5 priority tourist destinations in Indonesia. Through the results of research that has been stated that the success of developing tourist destinations depends on the concept of tourism, the tourist services and infrastructure offered are in accordance with the needs and desires of tourists, if the concept of tourism, tourism services and facilities and infrastructure offered are appropriate, then tourists will be motivated to continue to visit these tourist attractions.